Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Spatial Patterns and Predictors of Forest Carbon Stocks in Western Mediterranean - Vayreda, Jordi; Gracia, Marc; Canadell, Josep G; Retana, Javier (Ecosystems, 2012)
Mediterranean semi-arid forest ecosystems are especially sensitive to external forcing. An understanding of the relationship between forest carbon (C) stock, and environmental conditions and forest structure enable prediction of the impacts of climate change on C stocks and help to deﬁne management strategies that maximize the value of forests for C mitigation. Based on the national forest inventory of Spain (1997–2008 with 70,912 plots), we estimated the forest C stock and spatial variability in Peninsular Spain and, we determined the extent to which the observed patterns of stand C stock can be explained by structural and species richness, climate and disturbances. Spain has an average stand C stock of 45.1 Mg C/ha. Total C stock in living biomass is 621 Tg C (7.8% of the C stock of European forests). The statistical models show that structural richness, which is driven by past land use and life forest history including age, development stage, management activities, and disturbance regime, is the main predictor of stand tree C stock with larger C stocks in structurally richer stands. Richness of broadleaf species has a positive effect on both conifer and broadleaf forests, whereas richness of conifer species shows no signiﬁcant or even a negative effect on C stock. Climate variables have mainly an indirect effect through structural richness but a smaller direct predictive ability when all predictors are considered. To achieve a greater standing C stock, our results suggest promoting high structural richness by managing for uneven-aged stands and favoring broadleaf over conifer species.
Keywords: conifer and broadleaf forests; fire disturbance; Forest management; national forest inventory; Peninsular Spain; structural richness; tree carbon stock; Tree species richness; understory carbon stock; Water availability

Interspecific differences in sapling performance with respect to light and aridity gradients in Mediterranean pine–oak forests: implications for species coexistence - Zavala, MIGUEL a; Espelta, Josep M; Caspersen, John; Retana, Javier (Canadian Journal of Forest Research, 2011)
The relative abundance of two codominant Mediterranean tree species, shade-tolerant Quercus ilex L. and shade-intolerant Pinus halepensis Mill., is inversely correlated along aridity gradients, but this pattern is not explained by seedling responses to water or light availability, suggesting that subsequent life history stages may explain forest composition. To test this hypothesis, we calibrated statistical models of sapling growth and height–diameter allometry as functions of light availability and climatic variation as well as models of sapling mortality as a function of growth history. Contrary to the expectation of a sun–shade growth trade-off, P. halepensis grew faster than Q. ilex saplings at both low and high light levels. Low precipitation and aridity suppressed sapling growth rates, but no evidence of a shade–drought growth trade-off was found either. Pinus halepensis sapling mortality was strongly growth dependent, exhibiting high mortality rates at low growth, but the mortality of Q. ilex saplings was not. Height–diameter allometric variation was higher in low- than in high-light environments and was more pronounced with respect to changes in light than climatic water. Our results suggest that interspecific differences in sapling mortality and plasticity, rather than growth, may control species distributions at the mesic end of the aridity gradient.
doi: 10.1139/x11-050
Keywords: growth (voyant); light; Pinus halepensis; Quercus ilex; sapling mortality; Water availability

Masting mediated by summer drought reduces acorn predation in mediterranean oak forests - Espelta, Josep Maria; Cortés, Pilar; Molowny-Horas, Roberto; Sánchez-Humanes, Belén; Retana, Javier (ECOLOGY, 2008)
Temporally variable production of seed crops by perennial plants (masting) has been hypothesized to be a valuable mechanism in the reduction of seed predation by satiating and starving seed consumers. To achieve these benefits, coexisting species subjected to the same predator would benefit from a similar pattern of seeding fluctuation over time that could lead to a reduction in predation at the within-species level. We tested for the existence of an environmental factor enforcing synchrony in acorn production in two sympatric Mediterranean oaks ( Quercus ilex and Q. humilis) and the consequences on within-species and between species acorn predation, by monitoring 15 mixed forests (450 trees) over seven years. Acorn production in Q. ilex and Q. humilis was highly variable among years, with high population variability (CVp) values. The two species exhibited a very different pattern across years in their initial acorn crop size ( sum of aborted, depredated, and sound acorns). Nevertheless, interannual differences in summer water stress modified the likelihood of abortion during acorn ripening and enforced within-and, particularly, between-species synchrony and population variability in acorn production. The increase in CVp from initial to mature acorn crop ( after summer) accounted for 33% in Q. ilex, 59% in Q. humilis, and 60% in the two species together. Mean yearly acorn pre-dispersal predation by invertebrates was considerably higher in Q. humilis than in Q. ilex. Satiation and starvation of predators was recorded for the two oaks, and this effect was increased by the year-to-year variability in the size of the acorn crop of the two species combined. Moreover, at a longer time scale ( over seven years), we observed a significant reduction in the mean proportion of acorns depredated for each oak and the variability in both species' acorn production combined. Therefore, our results demonstrate that similar patterns of seeding fluctuation over time in coexisting species mediated by an environmental cue ( summer drought) may contribute to the reduction of the impact of seed predation at a within-species level. Future research should be aimed at addressing whether this process could be a factor assisting in the coexistence of Q. ilex and Q. humilis.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: Curculio spp.; fruit abortion; fruiting synchrony; Mediterranean mixed-oak forests; oaks; predator satiation; Quercus humilis; Quercus ilex; resource matching

Masting mediated by summer drought reduces acorn predation in mediterranean oak forests - Espelta, Josep Maria; Cortés, Pilar; Molowny-Horas, Roberto; Sánchez-Humanes, Belén; Retana, Javier (ECOLOGY, 2008)
Temporally variable production of seed crops by perennial plants (masting) has been hypothesized to be a valuable mechanism in the reduction of seed predation by satiating and starving seed consumers. To achieve these benefits, coexisting species subjected to the same predator would benefit from a similar pattern of seeding fluctuation over time that could lead to a reduction in predation at the within-species level. We tested for the existence of an environmental factor enforcing synchrony in acorn production in two sympatric Mediterranean oaks ( Quercus ilex and Q. humilis) and the consequences on within-species and between species acorn predation, by monitoring 15 mixed forests (450 trees) over seven years. Acorn production in Q. ilex and Q. humilis was highly variable among years, with high population variability (CVp) values. The two species exhibited a very different pattern across years in their initial acorn crop size ( sum of aborted, depredated, and sound acorns). Nevertheless, interannual differences in summer water stress modified the likelihood of abortion during acorn ripening and enforced within-and, particularly, between-species synchrony and population variability in acorn production. The increase in CVp from initial to mature acorn crop ( after summer) accounted for 33% in Q. ilex, 59% in Q. humilis, and 60% in the two species together. Mean yearly acorn pre-dispersal predation by invertebrates was considerably higher in Q. humilis than in Q. ilex. Satiation and starvation of predators was recorded for the two oaks, and this effect was increased by the year-to-year variability in the size of the acorn crop of the two species combined. Moreover, at a longer time scale ( over seven years), we observed a significant reduction in the mean proportion of acorns depredated for each oak and the variability in both species' acorn production combined. Therefore, our results demonstrate that similar patterns of seeding fluctuation over time in coexisting species mediated by an environmental cue ( summer drought) may contribute to the reduction of the impact of seed predation at a within-species level. Future research should be aimed at addressing whether this process could be a factor assisting in the coexistence of Q. ilex and Q. humilis.
Keywords: Curculio spp.; fruit abortion; fruiting synchrony; Mediterranean mixed-oak forests; oaks; predator satiation; Quercus humilis; Quercus ilex; resource matching

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain - Broncano, Maria José; Retana, Javier; Rodrigo, Anselm (Plant Ecology, 2005)
Quercus ilex and Pinus halepensis are two of the most common tree species of the western Mediterranean basin. Both species regenerate reliably after ﬁre: P. halepensis colonizes recently disturbed areas by eﬀective seedling recruitment, while Q. ilex resprouts vigorously after disturbances. For this reason, the natural regeneration of these species after ﬁre should ensure the re-establishment of a forest similar to that which existed before the ﬁre. This study analyzes with a simple simulation model whether or not the relative abundance of monospeciﬁc and mixed forests of these species in the landscape is altered by ﬁre. We also analyze the topographic factors and the forest structure before the ﬁre that determine the changes in forest composition after ﬁre. This study has been carried out in a large ﬁre that occurred in NE Spain. Overall, 33% of plots changed to another community type, but this probability of change varied considerably among community types before the ﬁre. Monospeciﬁc forests of P. halepensis or Q. ilex had a high probability of remaining in their original composition after the ﬁre, whereas the resilience of mixed forests of these two species was quite low. Mixed forests changed for the most part to monospeciﬁc P. halepensis or Q. ilex forests. Analysis of several factors determining these changes indicated that only elevation as a signiﬁcant topographical variable. The eﬀect of ﬁre was to increase the altitudinal diﬀerentiation between the two species. P. halepensis forests that changed to mixed or Q. ilex forests were those of highest elevation, while the mixed and Q. ilex plots that changed to P. halepensis forests were those located at the lowest elevations. Concerning structural variables before ﬁre, density of Q. ilex trees before the ﬁre showed a much greater eﬀect than P. halepensis density in determining the post-ﬁre community. Finally, burn severity also inﬂuenced the changes observed. For both P. halepensis and Q. ilex forests, plots that changed to another forest type were mainly those that burned more severely. In the case of mixed forests, even low ﬁre severities involved high probabilities of change to monospeciﬁc forests.
Keywords: burn severity; mediterranean forest; natural regeneration; post-fire recovery; resilience

Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain - Broncano, Maria José; Retana, Javier; Rodrigo, Anselm (Plant Ecology, 2005)
Quercus ilex and Pinus halepensis are two of the most common tree species of the western Mediterranean basin. Both species regenerate reliably after ﬁre: P. halepensis colonizes recently disturbed areas by eﬀective seedling recruitment, while Q. ilex resprouts vigorously after disturbances. For this reason, the natural regeneration of these species after ﬁre should ensure the re-establishment of a forest similar to that which existed before the ﬁre. This study analyzes with a simple simulation model whether or not the relative abundance of monospeciﬁc and mixed forests of these species in the landscape is altered by ﬁre. We also analyze the topographic factors and the forest structure before the ﬁre that determine the changes in forest composition after ﬁre. This study has been carried out in a large ﬁre that occurred in NE Spain. Overall, 33% of plots changed to another community type, but this probability of change varied considerably among community types before the ﬁre. Monospeciﬁc forests of P. halepensis or Q. ilex had a high probability of remaining in their original composition after the ﬁre, whereas the resilience of mixed forests of these two species was quite low. Mixed forests changed for the most part to monospeciﬁc P. halepensis or Q. ilex forests. Analysis of several factors determining these changes indicated that only elevation as a signiﬁcant topographical variable. The eﬀect of ﬁre was to increase the altitudinal diﬀerentiation between the two species. P. halepensis forests that changed to mixed or Q. ilex forests were those of highest elevation, while the mixed and Q. ilex plots that changed to P. halepensis forests were those located at the lowest elevations. Concerning structural variables before ﬁre, density of Q. ilex trees before the ﬁre showed a much greater eﬀect than P. halepensis density in determining the post-ﬁre community. Finally, burn severity also inﬂuenced the changes observed. For both P. halepensis and Q. ilex forests, plots that changed to another forest type were mainly those that burned more severely. In the case of mixed forests, even low ﬁre severities involved high probabilities of change to monospeciﬁc forests.
Keywords: burn severity; mediterranean forest; natural regeneration; post-fire recovery; resilience

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

CARACTERIZACION ESTRUCTURAL DE LOS ENCINARES DE CATALUÑA Marc - Gracia, Marc; Retana, Javier; Espelta, Josep Maria; Gené, Caries (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, a characterization of structure of holm-oak forests in the Northeastem Iberian Peninsula is proposed. The study is based on different features of these forests, both at the stand and at the individuallevel.
Keywords: Basal area; density of stems; Forest structure; holm-oak; Quercus ilex; size distri bu ti on